Rationality And Survival Of Life Of Pi Reflected In Yann Martel's Life Of Pi Novel (2001): An Individual Psychological Approach - Sari , Devi Ratna (2013)
This study is aimed to show rationality and survival of Piscine Molitor Patel act in Life of Pi novel by using an individual psychological approach. It is done by establishing two objectives: the first is analyzing the novel based on its structural elements and the second is analyzing the novel based on the Individual Psychological Approach.This research is descriptive qualitative research. Type of data of the study is text taken from two data sources: primary and secondary. The primary data sources is Life of Pinovel written by Yann Martel published in 2001. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis.The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization,plot, setting, point of view, theme, styles are related to each other and form a unity. Second, based on the Individual Psychological analysis reflected in the character and characterization in fictional finalism, inferiority feelings and compensation, striving for superiority, social interest, style of life, and creative power of self form a solid unity. The last, based on rationality and survival analysis are focused on Piscine Molitor Patel as the major character of Life of Pi, human used their rationality and survival in their life.